African, Asian or Indian enigma, the East Asian Helicobacter pylori: facts or medical myths - GRAHAM, David Y (2009)
Helicobacter pylori is etiologically related to peptic ulcer disease and gastric adenocarcinomas. Reports of geographical enigmas (African, Asian, Indian and Costa Rican enigmas) are based on perceptions that clinical presentations in a population or region are not as the authors expected. We discuss the background for these enigmas and examine the evidence whether they are real or are medical myths. The African enigma was challenged almost as soon as it was proposed and recent analyses of endoscopic data have confirmed it is a myth, as H. pylori-related diseases occur in Africa at the expected frequencies. The Asian and Indian enigmas relate to gastric cancer and peptic ulcers, respectively, and when one takes the patterns of gastritis in the different regions, these enigmas disappear. The pattern of gastritis underlies and predicts the clinical outcome and the predominant pattern of gastritis has been observed to change much more rapidly than can be accounted for by changes in host genetics. There is also no evidence that these changes relate to changes in the predominant H. pylori strain. The factors that link most closely to preventing an atrophic corpus are environmental, with food preservation and diet currently assuming the most prominent roles. This focus on diseases (cancer vs duodenal ulcers) instead of the underlying patterns of gastritis has fostered, and possibly helped to perpetuate, these mythical enigmas. We suggest that a better strategy would be to focus on the pathogenesis of underlying histopathologic differences which could also lead to the identification of specific chemoprevention strategies.